Peningkatan Kualitas Informasi Kelompok Tani Binaan Balai Penyuluhan Pertanian Pandak Melalui Aplikasi Identitas Digital Dutataniku - Wibowo, Argo; Delima, Rosa; Chrismanto, Antonius Rachmat (Jurnal Pengabdian Teknik dan Ilmu Komputer (Petik), 2024)
Agriculture is one of the most important area in Indonesia. The agricultural area is also important in supporting national food security. Indonesia has quite a lot of potential for farmer resources, but the problem is that regeneration of millennial farmers has decreased. The purpose of this community service is the implementation of the DutaTani system which has been developed since 2016. Dutataniku is one of the applications in the DutaTani system in the form of a modern agricultural portal that starts from processing farmer information structures and learning information. UKDW Faculty of Information Technology together with the partner of the Balai Penyuluh Pertanian (BPP) Pandak Bantul invite young farmers to participate in advancing the agricultural area through training on the use of the Dutataniku application. Participatory learning methods are used in learning activities with farmers so that it can be seen how well the application is and its benefits for farmers. At the end of the activity, the use of applications and surveys was carried out with a success rate of application functionality at 90.95% and 83% of users agreed that the Dutataniku application was able to bring users better in managing and accessing agricultural information. This is of course related to improving the quality of information managed by users.